Factors for implementing green supply chain management in the construction industry - Mochamad Agung Wibowo; Naniek Utami Handayani; Anita Mustikasari (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: The objectives of this study are to elaborate on the concepts, dimensions and elements of green supply chain management (GSCM) and develop a framework of GSCM implementation for the construction industry. Design/methodology/approach: This paper presents the findings from a study where experts were asked to contribute their opinions related to GSCM in the construction industry. To develop the model, the Delphi method was used. The objective of this method is to achieve the most reliable consensus in a group of experts. Findings: The research result is a developed framework for GSCM in the construction industry comprising five concepts, 22 dimensions, and 82 elements. Research limitations/implications: The limitation of this research is that its output was the discovered elements, but it did not cover the implementation of this model in construction projects, so some elements may be missing. Practical implications: The output of the research could give new perspective to manage the construction project based on Green Supply Chain Method. Social implications: The stakeholder of the construction project has to learn with this concept (Green Supply Chain) in order to improve construction's project performance. Originality/value: The originality of this research is that it is a new theme in the area of the construction supply chain. Previous research merely considered the concept of GSCM in construction. Therefore, this research develops an assessment model for performance indicators of GSCM implementation in construction projects.
Keywords: 650; green supply chain management; construction industry; construction waste; project life cycle